Review on Boiling Heat Transfer Enhancement of Surfactant Solutions - Hu Zicheng; Wang Qian; Li Changfeng; Song Xinnan; Wang Yinghui (Zhileng xuebao)
A detailed review on boiling heat transfer enhancement by surfactant additives are presented in this paper to show the characteristics, bubble behaviors and correlations of boiling heat transfer of surfactant solutions. The results point out that the effects of interfacial adsorption, molecular structures, viscosity and soluble characteristics on boiling heat transfer of surfactant solutions are related to the surfactant ionic natures and concentrations of surfactant solutions in present literature. However, the influences of steam carrying, cloud point, heating method, boiling pressure and parameter coupling on boiling heat transfer of surfactant solutions are not well understood at present. In the aspect of bubble behaviors, the existing literatures show that the bubble behaviors of surfactant solutions are quite different from that of water and more emphasis should be put on the theoretical study. In addition, the boiling heat transfer correlations of surfactant solutions in the open papers exist the deficiency of less experimental data for verification and model parameters difficult to be determined. At last, some aspects that need to be investigated further and some new ideas in these fields are presented.